SMART GRIDS – GENERAL REVIEW OF SYNCHRONIZATION TECHNIQUES - Lipnicki, Piotr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
This paper deals with crucial aspect of synchronization in modern power grids. It presents the concept of intelligent networks (“smart grids”), as the future of today’s grid infrastructure. The diversity of different grid codes in regards to the synchronization requirements for different Transmission System Operators (TSO) is discussed. This paper shows the applications of synchronizing algorithms, their role in power grid system.. The methods are classified according to application, the reference frame used and the possibility of using them in single and three phase systems. Proper selection of synchronization algorithms to meet the requirements of TSO’s calls for creation of appropriate evaluation methods. For this reason, at the end of the article quality criteria for the evaluation of synchronizing algorithms were proposed and explained in detail. Finally, the last section states what are the most commonly used methods for grid synchronization.